Effects of design parameters on a multi jet impinging heat transfer - Culun, Perihan; Celik, Nevin; Pihtili, Kazim (Elsevier Science Inc, 2018)
The main focus of this work is a synergistic heat transfer analysis of the impinging multi jets. The geometry of the jet holes, arrangement of those holes, density of the jets through spanwise and streamwise directions and type of the confinement are the design parameters that affect the impingement characteristics. The numerical analysis is run by using commercial software ANSYS-CFX that uses computational fluid dynamics (CFD) codes. The average Nusselt number is extracted as the heat transfer result. It is concluded that, the heat transfer distribution under the densest-array jet impingement inside the one-exit-confined channel is behaved as the single jet because of the strong adjacent jet interference. The highest jet impingement heat transfer is achieved for the case using square jets. The effect of jet arrangement seems to be the weakest parameter on the heat transfer. (C) 2018 Faculty of Engineering, Alexandria University. Production and hosting by Elsevier B. V.
Keywords: Multi jet impingement; Computational fluid dynamics CFD; ANSYS-CFX